Collection of Pedagogical Notebooks for project work with arts (Praxis Educativa, 2026)
This article analyzes the lack of textbooks for arts subjects in the Chilean school system and relates it to the weak initial and ongoing training of teachers, especially in the public system. In response to this gap, it examines the Pedagogical Notebooks collection from the Ministry of Cultures, Arts, and Heritage as a complementary resource for strengthening teaching in and through the arts. It describes its structure, aligned with the school curriculum, based on theoretical frameworks, curated works, interdisciplinary projects, and national artistic references. Furthermore, it presents the results of a teacher evaluation that highlights its pedagogical utility, flexibility, and relevance for interdisciplinary work, and links this experience to the 2024–2029 Arts Education Policy. It concludes that these materials contribute to a contextualized and high-quality arts education and offer a potentially replicable model in Latin America.
Keywords: art education; curriculum; teaching materials; teacher training; interdisciplinarity